Decision making by the values of generalized average fuzzy functions - Kosareva, Natalja; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2012)
Notions of point, interval and triangular intuitionistic fuzzy numbers are introduced. The generalized weighted averaging operator is used for solving multiple criteria decision making problems. Monte Carlo study was conducted with the aim to establish for which types of intuitionistic fuzzy numbers and which exponent values of weighted generalized average operator probabilities of alternatives ranking errors are the least.